Considerations and Technical Pitfalls in the Employment of the MTT Assay to Evaluate Photosensitizers for Photodynamic Therapy - Carreño, Edith Alejandra (2021)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Comunicação Celular. Rio de Janeiro, RJ, Brasil / School of Health Sciences, National Open and Distance University UNAD. Bogota, Colombia.